MOTIVASI IBU MELAKUKAN IVA TEST. APAKAH DUKUNGAN SUAMI MEMILIKI PENGARUH? - Saad, Rahmiyani; Ramli, Kamrianti; Sulistiyowati, Sulistiyowati; Hikmawati, Noviana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The Visual Inspection with Acetic Acid (IVA) test is a simple and effective screening method for the early detection of precancerous cervical lesions. Motivation is one of the psychological factors that plays an important role in encouraging health behaviors, including women of childbearing age's desire to undergo IVA (Visual Inspection with Acetic Acid) testing. The purpose of this study was to determine the relationship between husband support and mothers' motivation to undergo IVA testing. The study design used in this research is cross-sectional. The study was conducted at the Bangetayu Community Health Center. The study was conducted in February 2024. The population consists of all married women aged 19–40 years residing in the Bangetayu Community Health Center service area. The study sample comprised 100 respondents. The sampling technique used was simple random sampling. The research instrument used a questionnaire. Data analysis was conducted using univariate and bivariate methods. The results showed a significant relationship between spousal support (p-value: 0.001) and the motivation of mothers to undergo IVA testing. It is recommended that the health center provide education on cervical cancer prevention to husbands as well, so that husbands can better understand and motivate their wives to undergo regular IVA tests.Keywords: IVA Test, Motivation, Husband.